ANALISA PENGUNGKAPAN LAPORAN KEUANGAN KOTA BANDA ACEH DENGAN OPINI WAJAR TANPA PENGECUALIAN (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2012)
Research to analyze the importance of disclosure (disclosure) is complete, so obtaining anunqualified assessment (WTP) to the Financial Statements by the city Banda Aceh. thatresearch can dikemukaan Disclosure Financial Statements presented in Banda Aceh hasprovided revealing information that should be disclosed in the presentation FinancialStatements. It can be seen from the results of the analysis carried out on budget realizationreport, found the quality of disclosure of revenue, expenditure and financing in the form ofgoods and services is very good. For disclosure of the balance of the city of Banda Aceh hascompiled the balance sheet classifications set by SAP. Then, the Cash Flow Statement, hasrevealed major groups separately receipts and gross cash from operating activities, investingnon-financial assets, and non-budget financing. For disclosure Achieving FinancialPerformance, 4 (four) financial performance disclosure items in the notes to the financialstatements, revealing description of Banda Aceh and other strategies used and the proceduresthat financial performance has been developed and implemented management. And forPresentation of Financial Statements and Accounting Policies, of 22 (twenty two) disclosureitems, has revealed 11 (eleven) the disclosure item regarding the reporting entity, basis ofaccounting, the basis of measurement, recognition of revenue and expenditure recognition,the establishment of a reserve fund as well as information other.Keywords: Disclosure, unqualified